What Is the Role of AI in Teleradiology Services? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2016)
Teleradiology, the practice of interpreting medical images remotely, has become an indispensable component of modern healthcare delivery. It addresses geogra...
Keywords: Telemedicine and Digital Health; Teleradiology; Services; Artificial Intelligence; Machine Learning; Deep Learning; Healthcare